Willa Cather's Pittsburgh - Cather, Willa 1873-1947 (Universit of Nebraska Press, 2021)
Cather Studies, Volume 13 explores the myriad ways Willa Cather's writing career was shaped by the decade she lived in Pittsburgh (1896-1906) and the artistic, professional, and personal connections that she made while sojourning there through 1916..
Description based on publisher supplied metadata and other sources
Keywords: Cather, Willa / 1873-1947 / Knowledge and learning; Cather, Willa,-1873-1947-Knowledge and learning; Electronic books; Aufsatzsammlung